The Effect of Clove Leave Essential Oil (Syzigium aromaticum, L) on Mortality Level of Aedes aegypty Mosquitos - Iva Ariska (Journal of Public Health and Pharmacy, 2023)
One of the big problems in Indonesia is dengue hemorrhagic fever caused by the Aedes aegypti mosquito. The use of natural materials as a safe control for health and environmentally friendly is an option for the community. Clove leaves contain compounds of eugenol, saponins, flavonoids, and tannins. The purpose of this study is to determine the effect of clove leaf essential oil, Syzygium aromaticum, L. on the level of Aedes aegypti Mosquito mortality. This is an experimental research which aims to determine the ability of clove leaf oil in the form of an electric diffuser to kill Aedes aegypti mosquitoes. The objects of this study are the Aedes aegypti mosquitos and clove leaf essential oil. The number of samples in this study was 250 mosquitoes and 500 ml of clove leaf essential oil. The data collection method in this study used primary data and secondary data. Based on the results of research that has been carried out on Aedes aegypti mosquitoes for 20 minutes of exposure and 24 hours holding with the treatment of 60 ml and 100 ml of clove leaf essential oil in two different chamber boxes, it can be concluded that clove leaf essential oil is Syzygium aromaticum, Linous. Can kill the Aedes aegypti mosquito and can be said to be effective. This study suggests that it is possible to establish cooperation so that in the future students can apply the knowledge that has been obtained to the community, in order to improve the degree of Public Health.